St James's Place tax guide 2010 - 2011 - Sinclair, Walter I.; Lipkin, E. Barry (Palgrave Macmillan, 2011)
The 39th annual edition of the leading guide to taxation in Britain. This practical and user-friendly guide is a bestseller with students, professionals, accountants and private individuals, explaining in simple terms how the UK tax system works and how best to minimise tax liabilities